Violence, community and writing. A possible "reading" of Juana Doña's testimony (Anclajes, 2023)
The aim of this article is to carry out a study of the work Desde la noche y la niebla (mujeres en las cárceles franquistas), a novel-testimony (1978), by Juana Doña,while using it as a platform and trigger for a debate about the broader genre of memorial narratives. To this end, we divide the analysis into three axes or tension nodes: violence (the effects it has on bodies, subjectivities, imaginaries, as well as its marked patriarchal component), community (the capacity of collective resistance of the prisoners, their strategies of opposition and survival in prison) and writing (especially, the possibilities of reading that exist in the presentto rescue the revolutionary potential of testimony). Inshort, we propose a study that illuminates three specific areas of Doña's work. Zones that connect with the rest of the prison narratives and that in one way or another continue some of the fundamental lines proposed by the memorialistic studies of the last decades.
Keywords: Juana Doña; Desde la noche y la niebla; violence; community; writing